A tale of two students: unpacking undergraduate mathematics students’ mathematical identities using the Listening Guide - Hall, Jennifer; Robinson, Travis; Flegg, Jennifer; Wilkinson, Jane (Educational Studies in Mathematics, 2025)
The lived experiences of university mathematics students are an emerging area of mathematics education research. In this article, we discuss findings from a study about the experiences of undergraduate students in mathematics degree programs at two Australian universities. We analyzed two participants’ interview data using the Listening Guide method, in order to unpack the various aspects, or voices, of each participant’s mathematical identity. Notably, when reporting our findings, we did not reveal the participants’ genders, to increase the focus on individual, rather than membership, identities. Although the participants had similar educational backgrounds and some commonalities in their mathematical identities, the ways that they enacted their mathematical identities differed widely. We argue that the Listening Guide is a valuable tool to draw out aspects of mathematical identities that may not otherwise be easily observed. Understanding the different ways that university mathematics students identify with and experience the field of mathematics during their university studies is a critical aspect of providing support for students. That is, it is only through understanding these identities and experiences that targeted, responsive supports can be provided.